A Study of Guideline for Learning and Teaching Development of Teachers and Students in Phrapariyattidhamma School - เหมัง, พระมหาอัมราช อมรเสวี; ศรีวิชัย, สุทธิพงษ์; แก้วทองใหญ่, ยุทธวีร์ (Journal of Educational Review Faculty of Education in MCU, 2018)
This Research had the objective as 1. To study of Learning and Teaching of Teachers and Students in Phrapariyattidham School Bangkok. 2. To study guideline for Development of Learning and Teaching of Teachers and Students in Phrapariyattidham School Bangkok. 3. To study the suggestions and guideline for Development of Learning and Teaching of Teachers and Students in Phrapariyattidham School Bangkok. The Research Method was question for teachers’ concept and students in Phrapariyattidham institute as concern about for Development of Learning and Teaching of Teachers. The example group from teachers and students in Phrapariyattidham institute as number 350 persons. The questions were taken for expertise 5 persons to prove value IOC and consistency value IOC as equals 0.8-1. After that took them to experiment with another group who were students in Phrapariyattidham at Thongdhammachat institute Klongsan District as number 30 pieces, and then could get confidence value from questionnaire as 0.863, and then took them recorded data with an example group as number 350 persons, and then took interview data from director of Phrapariyattidham as number 7 persons, can get a quality data by analyze statistic and mean as percentage and Standard Deviation, and the comparing with teachers and students concept from t-test and F-test by case study more than two groups by One Way ANOVA, and have significant as 0.05 with both way by Scheff by mean of a significant as 0.05. The results were found that: Learning and Teaching of Teachers and Students in Phrapariyattidham School Bangkok : Part for curriculum learning and teaching had found that, it had substance absolute for learning as the most revel and average value as 4.55 and had standard deviation as 0.64, after these the condition of curriculum had absolute and cause of timeless learning had found that as more revel too. An average as 3.88 and have standard deviation as 1.10 at lasting. Part for learning and teaching management had found that teacher names the objective for students to know every time and the questioners answers have satisfy as more revel and have significant as 4.45 and have standard deviation as 0.72. After that the condition for teachers have techniques teaching more style in one time as more revel too and had significant as 4.49 and have standard deviation as 7.67 at lasting. Part for learning and teaching when consider by each condition had found that teacher used media with more teaching as more revel and had significant as 4.41 and have standard deviation as 0.70. After that the condition as teacher uses environment media, that was made students analyzed and could be self-learning from fact as have more revel too and have significant as 4.49 and had significant as 0.79 at lasting. Part for evaluation from learning and teaching had found that teachers have evaluated every semester had more revel and had significant as 4.44 and have significant as 0.75. After that have conditions for evaluation from students’ activities absolutely with lesion plan as more revel significant as 4.20 and had significant as 0.81 at lasting.